Community Dermatology: Necessity or Hype? - Shrestha, Rushma (Europasian Journal of Medical Sciences, 2019)
Skin diseases are common all over the world with high prevalence in developing countries with significant socioeconomic and behavioral impact. In Nepal, it is the fourth leading cause of nonfatal diseases. A community clinic is a term used for a specialist clinic provided in a Primary Care setting. The aim of these clinics in Nepal is to improve access to basic health services including family planning, child health, and safe motherhood. But there are no policies for dermatological diseases in rural communities. As skin diseases do not usually cause mortality, it is often ignored. But the morbidity is often high and the impact on the quality of life is also high. Conducting regular skin camps at inaccessible parts of the country is a good way to provide service to the people of the community.